Wakaf Produktif Sebagai Upaya Peningkatan Ekonomi Perguruan Tinggi Swasta - Firmansyah, Kholis (Jihbiz : Jurnal Ekonomi, Keuangan dan Perbankan Syariah, 2017)
Private higher education institutions must always strive to improve their quality to produce graduates who are superior and competitive. In managing and developing private universities, of course, requires large funding. Relying on funding from students is not necessarily enough to manage and develop a private university. Meanwhile, minimal funding causes the economy of private universities to become unstable. In this case, productive waqf is an alternative as an effort to improve the economy of private universities. The collected waqf funds can then be developed and invested by Nadzir, who in this case is the manager of productive waqf in private universities, to various business sectors and investments that are lawful and productive, so that the profits can be used for the management and development of private universities so that the quality of higher education institutions. The private sector is getting more superior and competitive.